Fiscal Policy Effectiveness in Stabilizing Economic Cycles: A Time Series Analysis of Government Expenditure in Indonesia - Cynthia Brillyan Siahaan; Eva Yunita Munthe (JENOVA : Journal of Economics, Finance, Accounting, and Organizational Advancement, 2025)
Fiscal policy plays a central role in maintaining macroeconomic stability, particularly in emerging economies exposed to external shocks and domestic structural challenges. Focusing on Indonesia, this research analyzes the effectiveness of government expenditure in stabilizing economic cycles using quarterly time series data from 2000Q1 to 2023Q4. The empirical framework combines the Hodrick-Prescott filter to decompose real GDP into trend and cyclical components with the Vector Error Correction Model to examine short-run dynamics and long-run equilibrium relationships among government expenditure, tax revenue, GDP, and inflation. The Johansen cointegration test confirms the presence of long-run relationships among the variables, validating the use of the VECM approach. The estimation results show that government expenditure has a positive and statistically significant effect on GDP in both the short and long run. The estimated fiscal multiplier ranges from 0.82 to 1.62, with capital expenditure producing the strongest impact, reaching 1.35 in the short run and 1.62 in the medium run. Impulse Response Function analysis indicates that a positive government expenditure shock generates a persistent GDP response for approximately 8–12 quarters. Forecast Error Variance Decomposition further shows that government expenditure explains up to 30% of GDP fluctuations over the long horizon. Granger causality results reveal bidirectional causality between government expenditure and GDP, while the CUSUM test confirms model stability. These findings support the role of active fiscal policy as an effective instrument for economic stabilization in Indonesia.